Komplexe Koronardissektion bei Contusio cordis nach Polytrauma: Venoarterielle ECMO-unterstützte interventionelle Versorgung = Extended coronary dissection caused by severe polytrauma with contusio cordis : venoarterial ECMO-assisted percutaneous coronary intervention - Dreher, Michael; Beck, Grietje (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2016)
Treatment of a patient with acute cardiac failure due to a contusio cordis after polytrauma by an interdisciplinary team is reported. Shortly after admission to our shock room, the patient developed cardiogenic shock caused by an extended coronary dissection. After interim cardiopulmonary resuscitation, the patient was stabilized by venoarterial extracorporeal membrane oxygenation (ECMO) and subsequent complex coronary artery intervention in the heart catheter laboratory. Despite the increased left ventricular function which enabled partial weaning from the ECMO, the patient died of multiple organ failure 10 days after admission.